Outlook 2013 : absolute beginner's guide - Poremsky, Diane (Absolute beginner's guide (Indianapolis, Ind.), 2013)
A beginner's guide to Outlook 2013 provides a self-paced tutorial that introduces a variety of Outlook tasks and functions, as well as a number of shortcuts, tools, and techniques to simplify the use of the latest version of Outlook.